Pengaruh Pembelajaran Pendidikan Ekonomi terhadap Tingkat Literasi Keuangan Siswa Madrasah Aliyah Al-Barokah Mataram - Widyaningrum, Meiyanti; Yuniati, Musniasih (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2026)
This study aims to analyze the effect of Economics education on the financial literacy level of high school students. The study used a quantitative approach with an explanatory design. The subjects were high school students who had taken Economics education. Data were collected through a Likert-scale questionnaire measuring students' Economics education and financial literacy. Data analysis was conducted using descriptive statistics and simple regression analysis. The results showed that Economics education had a positive and significant effect on high school students' financial literacy levels. This finding indicates that the quality of Economics education plays a crucial role in improving students' understanding and ability to manage finances. The study's conclusions confirm that Economics education serves not only as a means of delivering academic material but also as a strategic tool in developing students' financial literacy competencies. The implications of this study demonstrate the importance of optimizing Economics education through a contextual and applicable approach. This study suggests the need to develop more innovative learning models and further research with more diverse approaches and variables to strengthen the financial literacy of the younger generation.